The Guru-UKM Method: Synergistic Effect of Hydrogel, Hydrofibre and Dermal Conservation in Burn Wound Management - Imran, Farrah-Hani; Ian, Chik; Kelly, Enda Gerard; Jarmin, Razman (IIUM Medical Journal Malaysia, 2018)
Initial wound care idioms were designed around a moist dressing in presumed better wound healing. As wound care advances, innovations of dressings were formed. In the Guru-UKM Method (GUM), we combined two well-established dressings producing a synergistic effect in burn wound management. Patients with deep partial thickness burns were selected for the GUM. From the time of admission, they receive 2 cycles of paraffin tulle dressings once every two days to allow demarcation, then are reassessed for suitability of the GUM technique. We discuss 7 different burn cases that presented to our Burn Unit from January 2014 – June 2015.All dressings should create a suitable moist environment for healing, yet should be a painless dressing to help the patient return to normal function as soon as possible. In burn wounds, a suitable dressing ideally also biochemically debrides fibrin and softens hardened eschar and slough, without necessitating the patient to undergo general anaesthesia and surgical debridement. The Guru-UKM Method is a combination dressing technique that facilitates optimal burn wound management.